6n-2=4n+6

Simple and best practice solution for 6n-2=4n+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n-2=4n+6 equation:


Simplifying
6n + -2 = 4n + 6

Reorder the terms:
-2 + 6n = 4n + 6

Reorder the terms:
-2 + 6n = 6 + 4n

Solving
-2 + 6n = 6 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-2 + 6n + -4n = 6 + 4n + -4n

Combine like terms: 6n + -4n = 2n
-2 + 2n = 6 + 4n + -4n

Combine like terms: 4n + -4n = 0
-2 + 2n = 6 + 0
-2 + 2n = 6

Add '2' to each side of the equation.
-2 + 2 + 2n = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 2n = 6 + 2
2n = 6 + 2

Combine like terms: 6 + 2 = 8
2n = 8

Divide each side by '2'.
n = 4

Simplifying
n = 4

See similar equations:

| 3x(x+5)= | | 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= | | 6a+12=2a-6 | | 8a-3b+2a+6b= | | 3y+5y=9y | | m^2+9m+7=-5+9(-5)+7 | | 5x^2+10x=40 | | w^2+7w=8 | | 2w^2+6w=8 | | 4x^2=-9x-5 |

Equations solver categories